2020
DOI: 10.3233/jad-200604
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Confinement on Neuropsychiatric Symptoms in Alzheimer’s Disease During the COVID-19 Crisis

Abstract: Background: Neuropsychiatric symptoms, such as depression, anxiety, apathy, agitation, and hallucinations, are frequent in Alzheimer's disease (AD) and their prevalence tends to increase with external stressors. Objective: We offer the first investigation of the effects of confinement during the COVID-19 crisis on neuropsychiatric symptoms in patients with AD. Methods: We contacted caregivers of 38 patients with AD who were confined to their homes for nearly two months and asked them to report whether patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
133
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(144 citation statements)
references
References 47 publications
6
133
1
4
Order By: Relevance
“…This is likely to be due to the lack of mental stimulation, which is linked with levels of cognition in dementia (Woods, Aguirre, Spector, & Orrell, 2012). Recent early evidence into cognitive and behavioural symptomatology in dementia since the pandemic supports this notion (Boutoleau-Bretonni ere et al, 2020;Canevelli et al, 2020), posing a large concern for the increased care needs of PLWD. Increased levels of dependency became particularly difficult for those unpaid carers who suddenly had to take over care that was usually provided by paid carers.…”
Section: Discussionmentioning
confidence: 99%
“…This is likely to be due to the lack of mental stimulation, which is linked with levels of cognition in dementia (Woods, Aguirre, Spector, & Orrell, 2012). Recent early evidence into cognitive and behavioural symptomatology in dementia since the pandemic supports this notion (Boutoleau-Bretonni ere et al, 2020;Canevelli et al, 2020), posing a large concern for the increased care needs of PLWD. Increased levels of dependency became particularly difficult for those unpaid carers who suddenly had to take over care that was usually provided by paid carers.…”
Section: Discussionmentioning
confidence: 99%
“…However, reduced social contact and physical activity during isolation may have also induced these changes. 55 Also, AD patients are more vulnerable to infection because it is difficult to restrict physical contact with others in situations that require physical care.…”
Section: Impact Of Covid-19 On Patients With Cognitive Impairmentmentioning
confidence: 99%
“… 77 Tele-counselling hotlines can aid in relieving suffering related to BPSD symptoms. In addition, family members often feel tired and stressed due to long-term care of dementia patients 55 66 ; thus, it is important to share the burden of care with other family members or caregivers. This can be accomplished by making “care and rest” schedules.…”
Section: Strategy For Managing Dementia During the Covid-19 Pandemicsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, these researches enrolled seniors without cognitive impairment. It was observed that the COVID-19 related confinement aggravated the behavioral and psychological symptoms of community-dwelling older adults with mild cognitive impairment (MCI) or mild dementia, with agitation, apathy, and aberrant motor activity being the most affected symptoms ( 29 , 30 ). A phone-based survey conducted by Goodman-Casanova et al ( 31 ) in order to explore the well-being and the physical and mental health impact in community-dwelling older adults with MCI or mild dementia during the quarantine also showed that 46.1% participants reported negative experiences, such as fear of become infected or infecting family members, frustration and boredom involving not being able to take part in daily activities, loss of usual routine and social isolation.…”
Section: Introductionmentioning
confidence: 99%